The Optic Canal: A Bottleneck for Cerebrospinal Fluid Dynamics in Normal-Tension Glaucoma? - Pircher, Achmed; Montali, Margherita; Berberat, Jatta; Remonda, Luca; Killer, Hanspeter E. (Frontiers in Neurology, 2017)
Purpose To report on the optic canal cross sectional area (OCA) in Caucasian patients with normal-tension glaucoma (NTG) compared with Caucasian control subjects without known optic nerve (ON) diseases. Methods: Retrospective analysis of computed tomographic (CT) images of the cranium and orbits in 56 NTG patients (30 females and 26 males; 99 of 112 eyes; mean age 67.7±11.1 years). 56 age- and gender matched subjects (mean age: 68.0±11.2 years) without known ON diseases served as controls. The OCA at the orbital opening was measured in mm² by using the tool “freehand”. Statistical analysis was performed by using the independent two-tailed t-test. Results: The mean orbital opening OCA in NTGs measured 14.5±3.5 mm², (right OCA: 14.4±3.6 mm2, left OCA: 14.5±3.4 mm²) and in controls 18.3±2.6 mm² (right OCA: 18.5±2.7 mm², left OCA: 18.1±2.5 mm2). The difference between NTG and controls was statistically significant (p<0.000 for the right OCA, p<0.000 for the left OCA). Conclusions: This study demonstrates narrower OCAs in Caucasian NTG patients compared to Caucasian control subjects without known optic nerve (ON) diseases. Narrower OCAs might contribute to a discontinuity of the cerebrospinal fluid (CSF) flow between the intracranial and orbital subarachnoid space (SAS) in NTG patients. This might have an influence onto the pathophysiology in NTG.